Implementation Analysis of Financial Report as PSAK 108 in PT. Prudential Life Insurance in Indonesia - Fatur Ramadhan, Muhammad Annazhi; Soumena, Yasin; Damirah (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2022)
The purpose of this study was to determine how the application of financial statements based on PSAK 108 on the financial statements of PT. Prudential Life Assurance in Indonesia, especially in the report on the underwriting surplus/deficit of tabarru' funds and the 2018-2021 financial position report, using a quantitative approach with a descriptive type of research. The results showed that the presentation of the financial statements of PT. Prudential Life Assurance in Indonesia, especially in the report of the underwriting surplus/deficit of the tabarru' fund of PT. Prudential Life Assurance in Indonesia in 2018-2020 there are differences with the report of the underwriting surplus/deficit of tabarru' funds of PT. Prudential Life Assurance in Indonesia in 2021, the difference is in different postal (account) names. Statement of financial position of PT. Prudential Life Assurance in Indonesia in 2018-2021 there are differences in the order of postal names (accounts). The form of application of financial statements based on PSAK 108 does not only regulate the name of the post (account) but in its application PSAK 108 also regulates the recognition, measurement, presentation, and transactions of sharia insurance. The report on the underwriting surplus/deficit of tabarru' funds and the statement of financial position of PT. Prudential Life Assurance in Indonesia in 2018-2021 in terms of applying the name of the post (account) has not fully implemented the underwriting surplus/deficit report of tabarru' funds and the statement of financial position based on PSAK 108, while in terms of recognition, measurement, presentation, and report of surplus/deficit underwriting fund tabarru' and statement of financial position of PT. Prudential Life Assurance in Indonesia in 2018-2021 has implemented a surplus/deficit underwriting report for tabarru' funds and a statement of financial position based on PSAK 108.